Bat with Firefly Hybridization for Optimal Allocation and Capacity of Distributed Generation in Distribution Network - RajeshKumar Samala (IAES International Journal of Artificial Intelligence (IJ-AI), 2022)
This article grants an effective technique to find optimal allocation and capacity of Distributed Generation (DG) in a Radial Distribution Network (RDN). An effective method is a combination of Bat Approach (BA) and Firefly Approach (FA). Primarily, the load-flow investigation of RDS is performed by using Backward/ Forward (BW/FW) sweep algorithm. Because of load variation, the voltage profile, Voltage Stability Index (VSI) and power losses are investigated. Following that, weak buses are acknowledged on the basis of the VSI and power loss factors and fixing the DG. For recognizing the optimal location of DG, the Bat algorithm is used. After the DG placement, the power loss and VSI is diminished and maximized the voltage profile of the scheme. The Firefly Algorithm (FA) is used to assess the optimal capacity of the DG.  This projected technique is executed utilizing MATLAB/Simulink software and verified on IEEE 33 standard distribution scheme. Then efficiency of projected method is observed and compared with base case, Gravitational Search Approach (GSA) and Bat Approach.